2022
DOI: 10.7717/peerj.14387
|View full text |Cite
|
Sign up to set email alerts
|

Marine or freshwater: the role of ornamental fish keeper’s preferences in the conservation of aquatic organisms in Brazil

Abstract: Background The use of ornamental fish as pets has important implications for the conservation of the species used in fish keeping, particularly in relation to overexploitation. Understanding ornamental fish keepers’ relationship with the hobby can provide important information for assessing the potential impacts of the activity. Here, we analyzed the profile of Brazilian ornamental fish keepers and evaluated their preferences and the implications of their choices. Methods Information was obtained by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Finally, colorfulness and phylogenetic proximity to humans correlated exclusively with societal attention. Colorfulness is an important proxy for the aesthetic value of biodiversity (Langlois et al, 2022) and has been shown to often match cultural and economic interests—for example, it was recently shown that colorful birds and fish are more frequently targeted in wildlife trade (Borges et al, 2022; Senior et al, 2022). Phylogenetic proximity to humans seemingly correlates with a range of traits including the degree of empathy and anthropomorphism toward species.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, colorfulness and phylogenetic proximity to humans correlated exclusively with societal attention. Colorfulness is an important proxy for the aesthetic value of biodiversity (Langlois et al, 2022) and has been shown to often match cultural and economic interests—for example, it was recently shown that colorful birds and fish are more frequently targeted in wildlife trade (Borges et al, 2022; Senior et al, 2022). Phylogenetic proximity to humans seemingly correlates with a range of traits including the degree of empathy and anthropomorphism toward species.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, colorfulness and phylogenetic proximity to humans correlated exclusively with societal attention. Colorfulness is an important proxy for the aesthetic value of biodiversity ( Langlois et al, 2022 ; Santangeli et al, 2023 ) and has been shown to often match cultural and economic interests—for example, it was recently shown that colorful birds and fish are more frequently targeted in wildlife trade ( Borges et al, 2022 ; Senior et al, 2022 ). Phylogenetic proximity to humans seemingly correlates with a range of traits including the degree of empathy and anthropomorphism toward species.…”
Section: Discussionmentioning
confidence: 99%
“…The ornamental fish trade, a significant subsector of the aquaculture industry, is valued at up to USD 15–30 billion annually [ 1 ]. Ornamental fish are the third most popular pet choice, and approximately 14% of households in Hong Kong keep ornamental fish [ 2 , 3 ]. With the limited local supply, ornamental fish are often imported from different producing countries, and Hong Kong is ranked as the 14th largest importer in 2022 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%